Study on reservoir fluid source and hydrocarbon accumulation process in deep to ultra-deep strike-slip fault zone: A case study of Fuman Oilfield, Tarim Basin - XUE Yifan, WEN Zhigang, HUANG Yahao, ZHANG Yintao, QIAO Zhanfeng, ZHANG Tianfu, LI Mengqin, WANG Peng (Youqicang pingjia yu kaifa)
The study of the filling veins in deep reservoirs within the strike-slip fault zone in the north of Fuman Oilfield utilizes a range of methods including petrographic characteristics, analysis of rare earth elements andSr（strontium） isotopes, fluorescence spectra of oil inclusions, microscopic thermodynamics, and U-Pb isotopic dating of carbonate rocks. The findings reveal two stages of calcite vein formation in this area. These veins originate from the formation water of the middle and Lower Ordovician sources, with no evidence of oxidizing fluid intrusion, suggesting that the deep to ultra-deep oil and gas reserves have maintained good sealing properties in later stages. Furthermore, based on the burial history deduced from inclusions and low U-Pb isotope dates from carbonate rocks, it has been determined that there are three distinct stages of hydrocarbon charging in the deep Ordovician strata of the northern strike-slip fault zone in the Tarim Basin. These stages correspond to （459±7.2） Ma（middle Caledonian）, （348±18） Ma（early Hercynian）, and 268 Ma（late Hercynian）. It is noted that the early Hercynian period was the key phase for hydrocarbon accumulation in the deep and ultra-deep carbonate rocks in the north of Fuman Oilfield, with a significant correlation observed between oil and gas charging and fault activity.